1994
DOI: 10.1007/bf01753841
|View full text |Cite
|
Sign up to set email alerts
|

Reduced E-cadherin expression correlates with increased invasiveness in colorectal carcinoma cell lines

Abstract: A reduction in cell adhesiveness and cell invasion are essential steps in tumour progression to metastasis. In the present study two out of seven colorectal carcinoma cell lines exhibited reduced expression of the cell-cell adhesion molecule E-cadherin as assessed by immunofluorescence. The same two cell lines were invasive in the collagen gel and membrane invasion culture system invasion assays. Addition of anti-E-cadherin antibody to a non-invasive carcinoma cell line caused the cells to assume a dissociated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…28 Recent studies have demonstrated that loss of E-cadherin immunoreactivity may correlate with a lack of differentiation and aggressive behavior of breast, head and neck, lung, gastric, esophageal, colorectal, prostatic and urothelial carcinomas. [5][6][7]15,[29][30][31][32][33][34][35] Published studies on urothelial carcinoma show that loss of membranous E-cadherin immunoreactivity is strongly correlated with high grade and advanced stage. 8,12,15,[36][37][38] Whether or not loss of E-cadherin is correlated with disease progression or has any prognostic significance has been debated by several investigators.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recent studies have demonstrated that loss of E-cadherin immunoreactivity may correlate with a lack of differentiation and aggressive behavior of breast, head and neck, lung, gastric, esophageal, colorectal, prostatic and urothelial carcinomas. [5][6][7]15,[29][30][31][32][33][34][35] Published studies on urothelial carcinoma show that loss of membranous E-cadherin immunoreactivity is strongly correlated with high grade and advanced stage. 8,12,15,[36][37][38] Whether or not loss of E-cadherin is correlated with disease progression or has any prognostic significance has been debated by several investigators.…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, downregulation of E-cadherin expression is associated with higher histological grade and a worse prognosis (Van Aken et al, 1993). Reduced E-cadherin expression in colon tumor cells allows cells to invade into collagen and Matrigel (Kinsella et al, 1994). Transcriptional regulation is one of the regulatory steps in controlling E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations in cell-cell adhesion are thought to be key events in the progression from localized malignancy to metastatic disease and several in-vitro studies have confirmed that E-cadherin acts as a tumour suppressor protein (Vleminckx et al, 1991;Kinsella et al, 1994). Reduced E-cadherin expression has been reported in a variety of human tumours and in many cases these changes correlate with advanced disease .…”
mentioning
confidence: 99%